If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + 1 = -5x + -24 Reorder the terms: 1 + 10x = -5x + -24 Reorder the terms: 1 + 10x = -24 + -5x Solving 1 + 10x = -24 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. 1 + 10x + 5x = -24 + -5x + 5x Combine like terms: 10x + 5x = 15x 1 + 15x = -24 + -5x + 5x Combine like terms: -5x + 5x = 0 1 + 15x = -24 + 0 1 + 15x = -24 Add '-1' to each side of the equation. 1 + -1 + 15x = -24 + -1 Combine like terms: 1 + -1 = 0 0 + 15x = -24 + -1 15x = -24 + -1 Combine like terms: -24 + -1 = -25 15x = -25 Divide each side by '15'. x = -1.666666667 Simplifying x = -1.666666667
| 2z^3-8z^2= | | 10+n=90 | | 2.5x+18=3.75x+11 | | 6x^4+8x^2-26x^3=0 | | 4(3*2)+18= | | 2m+8form=6 | | 5(x-6)+3=8 | | 11+15=81 | | (-2x+10)+(8x-1)= | | y-7=-2x+5 | | 3x+4y+22=4 | | 6x+.5y=-13 | | -3x+72=107+-10 | | 85=5x+5(x+3) | | 5y+3x+79=180 | | -20+3m=8m+5 | | 7b=3 | | 66-1x=-4x+78 | | (-4+6)+(x-5)= | | 3x+1y=3 | | (2w+9)(6+w)=0 | | 4p-8=5-2 | | 8k^2-80k^4=-192 | | 3b+a=225 | | -3.1u=7.7 | | 63=7x+4(x-9) | | 2x*5=13 | | x+(.75x)=700000 | | 60t-66=10t-90 | | 8y-3=16+2y | | 4x^2-420x+2744=0 | | 4x+3(x+2)-2(y-6)=0 |